2023
DOI: 10.21037/atm-22-6508
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of the diagnostic accuracy of the ultrasonic sign-score method and MRI for PA, PI and PP in high-risk gravid women: a retrospective study

Abstract: Background The diagnosis and management of placenta accrete spectrum (PAS) is a great challenge to obstetricians. Ultrasound (US) and magnetic resonance imaging (MRI) are two main methods to detect PAS. MRI has high resolution, but the examination fee is expensive. US machine and examination fee is cheap, but the resolution is relatively low. Balancing the cost and accuracy for PAS diagnosis is very important. Methods The ultrasonic sign-score method and MRI findings fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…It was confirmed that the diagnostic value of the ultrasound scoring system was higher than that of conventional ultrasound examination, and the combination of the 2 can effectively improve the sensitivity and accuracy of disease diagnosis, reduce the risk of missed diagnosis and misdiagnosis, and ensure that patients receive targeted intervention as soon as possible. [ 18 ] Ye et al [ 19 ] showed that the ultrasound scoring system is a comprehensive system of typical abnormal signs of disease, which is scored according to its severity, and the degree of implantation is evaluated by different scores; compared with the subjective qualitative diagnosis of conventional ultrasound, it is more standardized and comprehensive, and can avoid the shortage that the operator chooses different ultrasonic signs and endows different importance with implantation judgment due to personal operation technology and clinical experience, which can effectively reduce misdiagnosis and missed diagnosis rates. The ultrasound scoring system can predict the type and degree of implantation to guide patients in terminating pregnancy and effectively make preoperative preparations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It was confirmed that the diagnostic value of the ultrasound scoring system was higher than that of conventional ultrasound examination, and the combination of the 2 can effectively improve the sensitivity and accuracy of disease diagnosis, reduce the risk of missed diagnosis and misdiagnosis, and ensure that patients receive targeted intervention as soon as possible. [ 18 ] Ye et al [ 19 ] showed that the ultrasound scoring system is a comprehensive system of typical abnormal signs of disease, which is scored according to its severity, and the degree of implantation is evaluated by different scores; compared with the subjective qualitative diagnosis of conventional ultrasound, it is more standardized and comprehensive, and can avoid the shortage that the operator chooses different ultrasonic signs and endows different importance with implantation judgment due to personal operation technology and clinical experience, which can effectively reduce misdiagnosis and missed diagnosis rates. The ultrasound scoring system can predict the type and degree of implantation to guide patients in terminating pregnancy and effectively make preoperative preparations.…”
Section: Discussionmentioning
confidence: 99%
“…Such as multidisciplinary collaborative management, reasonable selection of surgical methods, etc. [ 19 , 20 ] At the same time, Yang et al [ 21 ] pointed out that ultrasound examination can determine the BF status of the cavity BF in the placental parenchyma and the junction of uterine serosa and bladder; the ultrasound scoring system can confirm whether the subject has PA at the thinnest part of the uterine myometrium with the help of conventional ultrasound signs and other information. The combination of the two can realize complementary advantages and disadvantages and effectively improve the value of disease diagnosis and treatment evaluation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation